2021
DOI: 10.3390/ijerph18073404
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of the COVID-19 Pandemic on Ambient Air Quality in China: A Quasi-Difference-in-Difference Approach

Abstract: The novel coronavirus (COVID-19) pandemic has provided a distinct opportunity to explore the mechanisms by which human activities affect air quality and pollution emissions. We conduct a quasi-difference-in-differences (DID) analysis of the impacts of lockdown measures on air pollution during the first wave of the COVID-19 pandemic in China. Our study covers 367 cities from the beginning of the lockdown on 23 January 2020 until April 22, two weeks after the lockdown in the epicenter was lifted. Static and dyna… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 59 publications
(61 reference statements)
0
8
0
Order By: Relevance
“…Nevertheless, not all evidenced an increase of the pollutants after the lockdown, because of the slow economic recovery [ 48 , 61 , 70 ]. Similarly, studies that compared to the same period in previous years [ 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 ], and even more robustly with historical data of more than 5 years ( Table 1 ), reported a decrease of pollutants’ concentrations during the lockdown. As shown in Table 1 , decreases between 9–60%, 21.4–61.6%, and 30–66% were obtained for PM 2 .…”
Section: Discussionmentioning
confidence: 60%
“…Nevertheless, not all evidenced an increase of the pollutants after the lockdown, because of the slow economic recovery [ 48 , 61 , 70 ]. Similarly, studies that compared to the same period in previous years [ 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 ], and even more robustly with historical data of more than 5 years ( Table 1 ), reported a decrease of pollutants’ concentrations during the lockdown. As shown in Table 1 , decreases between 9–60%, 21.4–61.6%, and 30–66% were obtained for PM 2 .…”
Section: Discussionmentioning
confidence: 60%
“…The empirical model assumes that in the absence of the pandemic, temporal changes in crash severity before and after the onset of the COVID-19 outbreak would be essentially the same in 2020. Therefore, the year 2020 is considered as the "treatment group," and the periods after the disruption in both 2019 and 2020 are considered as the "aftertreatment periods" (Zhang and Tang 2021;Vandoros 2021). A similar quasi-DID model with previous years as a control group has been utilized in previous studies when a control group is not available during a global pandemic (Vandoros 2020(Vandoros , 2021Zhang and Tang 2021).…”
Section: Methods and Datamentioning
confidence: 99%
“…Therefore, the year 2020 is considered as the "treatment group," and the periods after the disruption in both 2019 and 2020 are considered as the "aftertreatment periods" (Zhang and Tang 2021;Vandoros 2021). A similar quasi-DID model with previous years as a control group has been utilized in previous studies when a control group is not available during a global pandemic (Vandoros 2020(Vandoros , 2021Zhang and Tang 2021). Two "aftertreatment periods," specifically March-May and June-December, were used based on the timeline of the two phases of the pandemic (Jiao and Azimian 2021).…”
Section: Methods and Datamentioning
confidence: 99%
“…They found that the average CO surface concentration was reduced by 18.7% with a spatial variation of 8-27%. Zhang et al 26 monitored the air quality in China during the COVID-19 pandemic covering 367 cities from 23 January 2020 to April 22, 2020. Their study revealed that CO concentration dropped by 30% due to the adopted traffic restriction to cease the spread of viral transmission.…”
Section: Carbon Emission/concentration Over the Land Regionmentioning
confidence: 99%